AKIDAH DAN AKHLAQ ISLAM - Askahar Askahar (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
The background of this journal is that by seeing many generations now, they are not paying enough attention to how to implement noble character in their daily interactions. Morals and ethics are human behavior in everyday life that has been attached to someone. In this study, it consists of 5 problem formulations namely (1) what is moral and ethical understanding (2) how moral values in Islam (3) refer to and explain the distribution of morals (4) how to base morals and (5) write and explain moral character. With the aim to find out how moral values in Islam, the distribution of morals, the principles of morals and moral characteristics in Islam. The method of writing this journal is a descriptive method. In this paper the author discusses the notion of morals and ethics, values, division of morals, moral principles, and moral characteristics in Islam, this method of research methods that provide explanations using analysis. In its implementation, this method is more likely to focus more on the theoretical / legal basis. The results show: (1) what is the meaning of morals and ethics, namely morality concerning matters relating to good, bad, right and wrong actions in the actions of a human being whose role models come from the Qur'an and the Hadith of the Prophet. Whereas ethics originating from cultural results and customs in a place that prevails in a society (2) how moral values ​​in Islam are moral values ​​derived from the rules and revelations of Allah and the instructions of Rausl saw. (3) write and explain the division of morals namely morals are divided into two, namely noble morals (easy) means noble and despicable morals (mazmumah) means morals that are forbidden or disliked by Allah (bad deeds) (4) how moral principles are morals are things that are fair to every human being such as: a. Adab to God, b. Adab to the Messenger of Allah. c. respect the old and love the small (young) d. Be trusty e. reconcile those who disagree f. Enthusiasm and (5) write and explain moral characteristics, namely a. believe in Allah and follow the teachings of the Prophet Muhammad PBUH which is guaranteed to obtain happiness in the prayer and always exposes himself to Allah. c. avoid empty talk and vain creation, d. fulfill zakat to purify the soul, d. keep the sanctity of the biological relationship by not doing it except for what is lawful e) maintain the mandate entrusted to him f) fulfill the promise he made g) discipline in perform prayers h) tawadhu 'i) roomy against bodo people j) diligent k) fear of Allah and his punishment l) behave naturally m) clean from adultery n) do not want to be false witnesses o) do not want to fellowship with people who like to do things that are not useful, p) stay away from that action to welcome someone who invites goodness and accepts all advice.